(untitled) (Health Renaissance, 2011)
Background: The optimal method of humeral shaft fracture fixation remains debatable. With the dramatic success of intramedullary fixation for fractures of the femur and tibia, there was speculation that IM-ILN might be more appropriate for humeral shaft fractures than DCP. Objectives: To compare the fixation of fracture shaft of humerus with interlocking nail and dynamic compression plate in terms of duration of operating time, amount of blood loss, rate of infection, pain at the fracture site, time to achieve union, functional outcome (DASH score) and complications of surgery. Methods: This was randomised control trial study. All patients with fractures of shaft of humerus that met the criteria for operative interventions presenting to the Department of Orthopaedics, BPKIHS in the study period and giving informed consent were included in the study. Sample size was taken 30 in each group. Results: The usual mode of injury in both the groups were road traffiic accident followed by fall from height, work place injury. The operating time for nailing was 100 mins with standard deviation of 11.24 while that of humerus plating was 90.25 with standard deviation 15.6.The mean blood loss in nail group was 148.75 with standard deviation of 36.70 while that in plate group was 205.00 with standard deviation of 45.60. Post operative hospital stay was similar in both groups with mean stay of 4.5 days. DASH was significantly higher in plating group at 6,12,18 and 24 weeks follow up. This showed better functional outcome in nailing group. Conclusion: Dynamic compression plating is better than interlocking nail for fracture shaft of humerus. Keywords: shaft of humerus; interlocking nail; plate fixation DOI: http://dx.doi.org/10.3126/hren.v9i2.4974 Health Renaissance 2011: Vol.9 (No.2): 61-66